Objective Assessment of Corneal and Lens Clarity in Patients with COVID-19. Issue 12 (December 2021) - Aydemir, Emre; Aksoy Aydemir, Gozde; Atesoglu, Halil İbrahim and Goker, Yasin Sakir and Kiziltoprak, Hasan and Ozcelik, Kazim Caglar
Abstract : SIGNIFICANCE: The severe acute respiratory syndrome coronavirus 2 virus, which causes the coronavirus disease 2019 (COVID-19) pandemic, can bind to epithelial cells in the human cornea and conjunctiva, which may result in changes of corneal and lenticular densitometry. PURPOSE: We aimed to report the corneal and lenticular clarity of patients who had been diagnosed previously with confirmed infection of COVID-19. METHODS: This was a prospective, cross-sectional study. Fifty-three patients who had recovered from COVID-19 and 51 healthy individuals who had not had COVID-19 (control) were included in this study. Measurement of the corneal (at a corneal diameter of 12 mm) and lens densitometry of participants was performed using a Pentacam HR Scheimpflug imaging system. Three different optimal depths as anterior, central, and posterior layers and four concentric zones, consisting of diameters of 0 to 2, 2 to 6, 6 to 10, and 10 to 12 mm, were chosen to perform the corneal densitometric measurements. The mean lenticular densitometric values were calculated in zone 1 at 2.0 mm, zone 2 at 4.0 mm, and zone 3 at 6.0 mm by taking the central part of the pupil as reference point. RESULTS: When compared with the individuals in the control group, the corneal densitometry measurements in the patients in the COVID-19 group were considerably higher in anterior 0 to 2 mm, 2 to 6 mm, 6 to 10 mm zones and total diameter; center 0 to 2 and 2 to 6 mm zones and total diameter; posterior 0 to 2 mm zone; and total corneal 0 to 2 and 2 to 6 mm zones and total diameter ( P < .05, for each). When compared with the individuals in the control group, all of the lens densitometry measurements, except for those located in zone 1, were determined to be significantly higher among the patients in the COVID-19 group ( P < .05, for each). CONCLUSIONS: Significant alterations were found in corneal and lenticular densitometric values in patients who had had COVID-19. The virus could adversely affect cornea and lens transparency.